Vascular CXCR4 Limits Atherosclerosis by Maintaining Arterial Integrity: Evidence From Mouse and Human Studies. Issue 4 (25th July 2017) - Döring, Yvonne; Noels, Heidi; van der Vorst, Emiel P.C.; Neideck, Carlos; Egea, Virginia; Drechsler, Maik; Mandl, Manuela; Pawig, Lukas; Jansen, Yvonne; Schröder, Katrin; Bidzhekov, Kiril; Megens, Remco T.A.; et al.
Abstract : Background: The CXCL12/CXCR4 chemokine ligand/receptor axis controls (progenitor) cell homeostasis and trafficking. So far, an atheroprotective role of CXCL12/CXCR4 has only been implied through pharmacological intervention, in particular, because the somatic deletion of the CXCR4 gene in mice is embryonically lethal. Moreover, cell-specific effects of CXCR4 in the arterial wall and underlying mechanisms remain elusive, prompting us to investigate the relevance of CXCR4 in vascular cell types for atheroprotection. Methods: We examined the role of vascular CXCR4 in atherosclerosis and plaque composition by inducing an endothelial cell (BmxCreER T2 -driven)–specific or smooth muscle cell (SMC, SmmhcCreER T2 - or TaglnCre-driven)–specific deficiency of CXCR4 in an apolipoprotein E–deficient mouse model. To identify underlying mechanisms for effects of CXCR4, we studied endothelial permeability, intravital leukocyte adhesion, involvement of the Akt/WNT/β-catenin signaling pathway and relevant phosphatases in VE-cadherin expression and function, vascular tone in aortic rings, cholesterol efflux from macrophages, and expression of SMC phenotypic markers. Finally, we analyzed associations of common genetic variants at the CXCR4 locus with the risk for coronary heart disease, along with CXCR4 transcript expression in human atherosclerotic plaques. Results: The cell-specific deletion of CXCR4 in arterial endothelial cells (n=12–15) or SMCs (n=13–24) markedly increased atherosclerotic lesion formation in hyperlipidemic mice. Endothelial barrier function was promoted by CXCL12/CXCR4, which triggered Akt/WNT/β-catenin signaling to drive VE-cadherin expression and stabilized junctional VE-cadherin complexes through associated phosphatases. Conversely, endothelial CXCR4 deficiency caused arterial leakage and inflammatory leukocyte recruitment during atherogenesis. In arterial SMCs, CXCR4 sustained normal vascular reactivity and contractile responses, whereas CXCR4 deficiency favored a synthetic phenotype, the occurrence of macrophage-like SMCs in the lesions, and impaired cholesterol efflux. Regression analyses in humans (n=259 796) identified the C-allele at rs2322864 within the CXCR4 locus to be associated with increased risk for coronary heart disease. In line, C/C risk genotype carriers showed reduced CXCR4 expression in carotid artery plaques (n=188), which was furthermore associated with symptomatic disease. Conclusions: Our data clearly establish that vascular CXCR4 limits atherosclerosis by maintaining arterial integrity, preserving endothelial barrier function, and a normal contractile SMC phenotype. Enhancing these beneficial functions of arterial CXCR4 by selective modulators might open novel therapeutic options in atherosclerosis. Abstract : Supplemental Digital Content is available in the text.